Effects of a Sourcing Prompt and Conflicts in Reading Materials on Elementary Students' Use of Source Information. Issue 2 (17th February 2019) - Paul, Johanna; Stadtler, Marc; Bromme, Rainer
ABSTRACT: Due to the increasing educational use of the Internet, children in elementary school need to critically evaluate source information to judge the trustworthiness of information. Studies with adult readers show that sourcing prompts and mutually exclusive claims in reading materials promote the use of source information. However, little is known about how these facilitating factors affect early readers. Therefore, we investigated to what extent a sourcing prompt and mutually exclusive claims in reading materials influence elementary students' use of source information when completing a multiple documents task. Results reveal that a sourcing prompt enhances source citations but not source evaluations or memory for source-content links. Students reading mutually exclusive claims more often adhere to the position of a trustworthy source but do not include more source references into their written task products.